Detecting display energy hotspots in Android apps. (13th June 2017) - Wan, Mian; Jin, Yuchen; Li, Ding; Gui, Jiaping; Mahajan, Sonal; Halfond, William G. J.
Summary: The energy consumption of mobile apps has become an important consideration for developers as the underlying mobile devices are constrained by battery capacity. Display represents a significant portion of an app's energy consumption—up to 60% of an app's total energy consumption. However, developers lack techniques to identify the user interfaces in their apps for which energy needs to be improved. This paper presents a technique for detecting display energy hotspots—user interfaces of a mobile app whose energy consumption is greater than optimal. The technique leverages display power modeling and automated display transformation techniques to detect these hotspots and prioritize them for developers. The evaluation of the technique shows that it can predict display energy consumption to within 14% of the ground truth and accurately rank display energy hotspots. Furthermore, the approach found 398 display energy hotspots in a set of 962 popular Android apps, showing the pervasiveness of this problem. For these detected hotspots, the average power savings that could be realized through better user interface design was 30%. Taken together, these results indicate that the approach represents a potentially impactful technique for helping developers to detect energy related problems and reduce the energy consumption of their mobile apps. Abstract : Energy‐inefficient user interfaces are present in over 40% of mobile apps. The dLens approach is able to quickly detect these user interfaces and provide accurately prioritized lists to app developers to help guide their optimization efforts. The estimated energy savings that could be realized by optimizing these user interfaces average 18%.